2011
DOI: 10.1007/978-3-642-24800-9_38
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Emotional Semantics of Abstract Art Using Low-Level Image Features

Abstract: Abstract.In this work, we study people's emotions evoked by viewing abstract art images based on traditional low-level image features within a binary classification framework. Abstract art is used here instead of artistic or photographic images because those contain contextual information that influences the emotional assessment in a highly individual manner. Whether an image of a cat or a mountain elicits a negative or positive response is subjective. After discussing challenges concerning image emotional sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…On the path of research in affective image classification [19][20][21][22][23], the achieved accuracy rates are relatively low. Furthermore, the use of definition in "discrete" emotions also caused these experiments hard to reproduce in countries other than the United States.…”
Section: Methods and Materials 21 Emotion Theoriesmentioning
confidence: 99%
“…On the path of research in affective image classification [19][20][21][22][23], the achieved accuracy rates are relatively low. Furthermore, the use of definition in "discrete" emotions also caused these experiments hard to reproduce in countries other than the United States.…”
Section: Methods and Materials 21 Emotion Theoriesmentioning
confidence: 99%
“…Affective concepts were modeled using color palettes, which showed that the bag of colors and Fisher vectors (i.e., higher order statistics about the distribution of local descriptors) were effective [9]. Zhang et al [27] characterized shape through Zernike features, edge statistics features, object statistics, and Gabor filters. Emotion-histogram and bag-of-emotion features were used to classify emotions by Solli et al [24].…”
Section: Related Workmentioning
confidence: 99%
“…Researchers [9,11,18,23,25,26] investigated factors such as color, texture, composition, and simple semantics to understand emotions, but have not quantitatively addressed the effect of perceptual shapes. The study that did explore shapes by Zhang et al [27] predicted emotions evoked by viewing abstract art images through low-level features like color, shape, and texture. However, this work only handles abstract images, and focused on the representation of textures with little accountability of shape.…”
Section: Introductionmentioning
confidence: 99%
“…We select three kinds of cross-domain databases such as Abstract100, Abstract 280, and STL-10 database [15,16].…”
Section: Local Feature Extraction In Transfer Learningmentioning
confidence: 99%
“…And the F1-Measurement represents the harmonic mean between the index of Precision and Recall. In this experiment, we adopt each index as shown in Formula (16)(17)(18)(19).…”
Section: Two Kinds Of Target Object Classificationmentioning
confidence: 99%